Identification and structural characterization of a cDNA clone encoding a membrane-bound form of the polypeptide pheromone Er-1 in the ciliate protozoan Euplotes raikovi. - Miceli, C (1992)
In the ciliate Euplotes raikovi, the same cell that secretes the pheromone Er-1, a polypeptide of 40 amino acids derived from a precursor (prepro-Er-1) of 75 amino acids, also produces a polypeptide of 130 amino acids, of which the 75 residues at the carboxyl terminus are identical to those of prepro-Er-1 and the 55 residues at the amino terminus form a new sequence. This larger Er-1 isoform is retained in membranes, where it may function as a binding site for soluble Er-1 in a mechanism of autocrine secretion. Membrane-bound and soluble Er-1 are translated from two mRNAs that apparently originate from a common micronuclear and/or macronuclear gene through alternative elimination of intervening sequences. This finding suggests that single genes responsible for the generation of isoform diversity in polypeptide hormones are present even in single-celled eukaryotes.